Labour Standards in International Economic Law (Springer International Publishing, 2018)
The book offers a comprehensive perspective on the highly topical issue of protecting and promoting labour standards in international economic law and the globalized economy. For the purpose of an in-depth analysis of both the specific and the fundamental aspects in this regard, it combines views from specialized academics of the legal and political sciences as well as experienced practitioners. The contributions to this book do not only reveal recurring obstacles but also point at best practices and potential for synergies, providing important guidance for future research and practice in international economic and labour law and policy.